Self-construal and attribution styles of Filipino and Filipino-American basketball athletes - Evangelista, Roel Manuel L. (Animo Repository, 2004)
The collective constructionist theory by Kitayama et al. (1997) asserts that individuals from Western societies make self-enhancing attributions while individuals from Eastern societies make self-critical attributions. This study used that theory to know the attribution styles of athletes. It was predicted that Filipino-Americans would make self-enhancing attributions while Filipinos would make self-critical attributions for one's successful and unsuccessful performance in basketball (Kitayama et al., 1997). Self-construal scores (independent and interdependent) of Filipino-American and Filipino basketball athletes, with ages between 22 and 30 years old were determined by administering the Self-Construal Scale (Singelis, 1994). A semi-structured questionnaire was used to interview 36 athletes (18 Filipino-Americans and 18 Filipinos) to gather their attributions. The findings of the study did not fully support the hypothesis for both cultural groups made self-critical and self-enhancing attributions. Successful performances were attributed to internal, stable, controllable, and global factors while unsuccessful performances were attributed to external, unstable, uncontrollable, and specific factors. Self-enhancing attributions are necessary so athletes can continue their successes while self-critical attributions are also important for they have to constantly improve because sports is a competitive endeavor.